Reaction paths of phosphine dissociation on silicon (001) - Warschkow, O; Curson, N J; Schofield, S R; Marks, N A; Wilson, H F; Radny, M W; Smith, P V; Reusch, T C G; McKenzie, D R; Simmons, M Y (The Journal of chemical physics, 2016)
Using density functional theory and guided by extensive scanning tunneling microscopy (STM) image data, we formulate a detailed mechanism for the dissociation of phosphine (PH3) molecules on the Si(001) surface at room temperature. We distinguish between a main sequence of dissociation that involves PH2+H, PH+2H, and P+3H as observable intermediates, and a secondary sequence that gives rise to PH+H, P+2H, and isolated phosphorus adatoms. The latter sequence arises because PH2 fragments are surprisingly mobile on Si(001) and can diffuse away from the third hydrogen atom that makes up the PH3 stoichiometry. Our calculated activation energies describe the competition between diffusion and dissociation pathways and hence provide a comprehensive model for the numerous adsorbate species observed in STM experiments.